Przewrót w leczeniu choroby niedokrwiennej serca – rola kardiologii interwencyjnej = The revolution in the treatment of ischaemic heart disease – the role of interventional cardiology - Łukasz Wołowiec (Journal of Education, Health and Sport, 2016)
Wołowiec Łukasz, Banach Joanna, Rogowicz Daniel, Surowiec Agnieszka, Zukow Walery, Sinkiewicz Władysław. Przewrót w leczeniu choroby niedokrwiennej serca – rola kardiologii interwencyjnej = The revolution in the treatment of ischaemic heart disease – the role of interventional cardiology. Journal of Education, Health and Sport. 2016;6(1):271-280. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45357